2013
DOI: 10.1103/physrevd.88.103510
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar velocity decomposition, redshift space distortion, and velocity reconstruction in redshift surveys. II. Dark matter velocity statistics

Abstract: Massive spectroscopic redshift surveys open a promising window to accurately measure peculiar velocity at cosmological distances through redshift space distortion (RSD). In Paper I Zhang et al. [Phys. Rev. D 87, 063526 (2013)] of this series of work, we proposed decomposing peculiar velocity into three eigenmodes (v , v S , and v B ) in order to facilitate the RSD modeling and peculiar velocity reconstruction. In the current paper we measure the dark matter RSD-related statistics of the velocity eigenmodes th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 52 publications
7
95
0
Order By: Relevance
“…It has been robustly detected for the case of DM simulation particles [19,21]. Therefore it must also exist for DM halos [20].…”
Section: No Velocity Bias Atmentioning
confidence: 99%
“…It has been robustly detected for the case of DM simulation particles [19,21]. Therefore it must also exist for DM halos [20].…”
Section: No Velocity Bias Atmentioning
confidence: 99%
“…The measurement can be done using one's favorite velocity assignment method, such as the ones based on the Voronoi and Delaunay tessellations [1]. Throughout this paper, we restrict to the NP (nearest particle) method [12]. As discussed in paper I, sampling artifacts in other velocity assignment methods are similar, so results on the sampling artifact in the NP method also provide a useful reference for that in other methods.…”
Section: Detection Of the Sampling Artifact In Simulationsmentioning
confidence: 99%
“…These works found that its impact increases with decreasing number density. This behavior can be used to diagnose the sampling artifact [12,13]. For example, by comparing the velocity power spectrum P v of two halo populations at equal volume density, the difference in P v is significantly suppressed [13], manifesting the existence of a sampling artifact.…”
Section: Introductionmentioning
confidence: 99%
“…Recent, complementary, tests of models in Fourier space have been presented in Jennings, Baugh & Pascoli (2011); Blake et al (2011); Kwan, Lewis & Linder (2012); Okumura, Seljak & Descjacques (2012); Zheng et al (2013); Okumura et al (2014); Beutler et al (2014) and N-body based models for fitting the data to smaller scales have been presented in Reid et al (2014). The outline of the paper is as follows.…”
Section: Introductionmentioning
confidence: 99%